UNIVERSITIES AS LEARNING ORGANIZATIONS IN THE DIGITAL WORLD - Skiba М.А.; Turganbayeva А.Р. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article reveals the features of the development of universities as learning organizations operating in the digital world. The discrepancy between the formal understanding of the university, fixed in regulatory legal acts, and the real functions of a modern university is revealed. The analysis of the coincidence of the semantic series of the concepts "university" and "learning organization" is carried out. The teacher functions of a university, which is a learning organization, have been identified. Awareness by universities of the need for the preservation, accumulation and development of knowledge leads to the translation of non-formalized knowledge of individual employees into formalized descriptions and procedures. The stages of development of the university as a learning organization are proposed. It is concluded that not only the knowledge itself should be used within the university, but also knowledge about knowledge and the ability to manage it, in this case the university can be considered a learning organization.